The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1748-717x-6-20
|View full text |Cite
|
Sign up to set email alerts
|

Rotational IMRT techniques compared to fixed gantry IMRT and Tomotherapy: multi-institutional planning study for head-and-neck cases

Abstract: BackgroundRecent developments enable to deliver rotational IMRT with standard C-arm gantry based linear accelerators. This upcoming treatment technique was benchmarked in a multi-center treatment planning study against static gantry IMRT and rotational IMRT based on a ring gantry for a complex parotid gland sparing head-and-neck technique.MethodsTreatment plans were created for 10 patients with head-and-neck tumours (oropharynx, hypopharynx, larynx) using the following treatment planning systems (TPS) for rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
60
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 29 publications
10
60
2
Order By: Relevance
“…This value is comparable to previous studies on step-and-shoot IMRT that reported reductions of 12% to 20% [10,31] and studies on sliding-window IMRT that reported reductions of 40% to 55% [11,16]. As the number of MUs per treatment is correlated with the amount of scatter dose and leakage radiation, which could be important based on the induction of secondary malignancies [32,33], a decrease in the number of MUs achieved with VMAT is desirable.…”
Section: Discussionsupporting
confidence: 88%
“…This value is comparable to previous studies on step-and-shoot IMRT that reported reductions of 12% to 20% [10,31] and studies on sliding-window IMRT that reported reductions of 40% to 55% [11,16]. As the number of MUs per treatment is correlated with the amount of scatter dose and leakage radiation, which could be important based on the induction of secondary malignancies [32,33], a decrease in the number of MUs achieved with VMAT is desirable.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the helical radiation delivery method is associated with low-dose spread 6 to the normal lung and can potentially result in patterns of lung injury that might be different than those observed with conventional three-dimensional conformal radiotherapy or other SABR techniques (Figure 1). Lastly, HT requires an increased number of monitor units, as compared with a nonwedged conformal plan, 17 which might result in a substantial prolongation of the total treatment time. This can potentially impair the reproducibility and comfort of patients with abnormal breathing owing to coexisting chronic obstructive pulmonary disease (COPD).…”
Section: Introductionmentioning
confidence: 99%
“…A higher degree of conformity was observed with the inhomogeneous dose prescription with HT than with nine fields step-and-shoot IMRT, although the authors concluded that both modalities were clinically suitable for dose painting. On the other hand, several studies comparing rotational IMRT systems without dose escalation in patients with HNSCC have been reported in the literature [2530]. Most of them found significantly higher normal tissue dose sparing with HT than with RA [25, 28–30].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies comparing rotational IMRT systems without dose escalation in patients with HNSCC have been reported in the literature [2530]. Most of them found significantly higher normal tissue dose sparing with HT than with RA [25, 28–30]. Regarding target coverage, Stromberger et al reported only small differences comparing both modalities for unilateral and bilateral simultaneous integrated boost plans [28].…”
Section: Discussionmentioning
confidence: 99%